Koagulasi Lateks Menggunakan Sari Pati Umbi Gadung dengan Penambahan Asam Semut - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Rahmat Hidayat (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Gadung is one type of vine that does not get attention because it contains poison in the form of hydrogen cyanide (HCN) compounds. Gadung has a high economic value and its presence is easy to find, gadung plants have high productivity reaching 20 tons/ha when compared to cassava which is only 7.4 tons/ha. Coagulation using gadung tuber starch is natural-based coagulation that is safe for farmers even though it contains cyanide (HCN) which is toxic, but by washing hands after direct contact or after using gadung tubers, it will not be dangerous, so it is more environmentally friendly. and can be produced conventionally by farmers themselves. The aims of this study were (i) to determine the effect of giving gadung tuber starch with the addition of ant acid on latex coagulation, (ii) to get the best dose of giving various kinds of gadung tuber starch with the addition of ant acid for latex coagulation. This research was conducted in Simpang 4 Batuah Village, Raren Batuah District, East Barito Regency, Central Kalimantan Province from March to June 2020 using a completely randomized design with 5 treatments and 4 replications. The first treatment was (p1) 20 ml of gadung tuber starch, (p2) 40 ml of gadung tuber starch, (p3) 60 ml of gadung tuber starch, (p4) 80 ml of gadung tuber starch, and (p5) 100 ml of gadung tuber starch. The results showed that the clumping time, the weight of the latex cup, and the texture of the latex had a very significant effect, the color of the latex and the smell of the latex had no effect